2019
DOI: 10.1002/cncr.32027
|View full text |Cite
|
Sign up to set email alerts
|

Association between primary language, a lack of mammographic screening, and later stage breast cancer presentation

Abstract: Background Health determinants are known to influence the stage of breast cancer presentation, but it is unclear to what extent language affects stage. This study investigates whether non–English‐speaking (NES) patients present at a later stage than their English‐speaking (ES) counterparts and whether language is associated with mammographic screening. Methods This study was a retrospective, single‐institution cohort analysis of women undergoing breast radiotherapy from 2012 to 2017 (n = 1057). Patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Breast cancer is a serious threat to human health (1) and a major cause of morbidity and mortality among women, accounting for ~23% of female malignancies (2,3). With the development of medical technology and the prevalence of precancerous screening technology, breast cancer morbidity and mortality rates have declined in developed countries, but incidence and mortality are rising worldwide (4-6). Currently, the main treatment methods for breast cancer include surgical resection, radiotherapy and chemotherapy, as well as immunotherapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is a serious threat to human health (1) and a major cause of morbidity and mortality among women, accounting for ~23% of female malignancies (2,3). With the development of medical technology and the prevalence of precancerous screening technology, breast cancer morbidity and mortality rates have declined in developed countries, but incidence and mortality are rising worldwide (4-6). Currently, the main treatment methods for breast cancer include surgical resection, radiotherapy and chemotherapy, as well as immunotherapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…Differently, a large body of studies focuses on immigration status, which, particularly for recent immigrants, is demonstrated to negatively influence the rating for adherence to breast, cervical [29][30][31][32][33] and colorectal cancer screenings. 34,35 Difficulties related to the language represent one of the main obstacles, [36][37][38] along with cultural/religious beliefs. 39 These barriers are mainly reported whether culture/ religion are particularly sensitive towards "intimate areas" and "female body", 40 and cancer is considered as the unavoidable punishment for own sins.…”
Section: Background Informationmentioning
confidence: 99%
“…There is a paucity of data associating primary language and patients with non-English speaking backgrounds and outcomes in breast cancer. One single institution study from a quaternary care academic center demonstrated that non-English speaking patients comprised of 15% of the total cohort and were more likely to present at later stages (18).…”
Section: Outcome Disparitiesmentioning
confidence: 99%